Effect of Phenytoin Usage Duration Against Hs-Crp Levels in Epilepsy Patients - Ratna Wajiayanti1, Kurnia Kusumastuti1 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: Patients with epilepsy have a higher risk of death than the normal population. Epilepsy patients have increased mortality due to cardiovascular disease with standardized mortality ratios ranged between 1.2 and 2.5. The incidence of non-fatal coronary heart disease also increased significantly between 34% and 63%. Atherosclerosis as an inflammatory state has an important biomarker namely hs-CRP. Longterm use of phenytoin will have an effect on hs-CRP. hs-CRP is an atherosclerotic biomarker with a better cardiovascular predictor than blood lipid and homocysteine levels Methods: This study was conducted in epilepsy patients who fulfill ESR the criteria of inclusion and exclusion in Outpatient Unit of Dr. Soetomo General Hospital from October 2014 to April 2015. Patients were divided into a control group and case group. The control group was patients with hs-CRP levels <1.7 meanwhile, control group was >1.7. Tracking of phenytoin usage duration was performed in both groups. Results: Thirty-four subjects were enrolESR in this study which consisted of 21 males (61.76%) and 13 females (38.23%). The mean age of subjects in the case group was 31.6 + 12.6 years and control group was 26.52 + 11.3. Data of phenytoin usage duration and hs-CRP levels were analyzed. Conclusion: There was no significant difference between hs-CRP levels on phenytoin usage duration of >2 years and <2 years with p = 0.290